2004
DOI: 10.1016/j.jcrs.2004.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Predicting time to refractive stability after discontinuation of rigid contact lens wear before refractive surgery

Abstract: The time for contact lens-induced corneal changes to reach a steady state after cessation of lens wear is highly variable. Among the variables examined, including those indicating corneal warpage, the factor that correlated with the required time to refractive stability after discontinuation of RGP wear was the length of time of contact lens use. Patients who are long-term RGP wearers should be counseled that multiple visits will likely be required before a stable refraction is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The second part of this study focused on changes to the corneoscleral profile in keratoconus eyes with regular specialty lens wear. Corneal warpage related to small-diameter corneal lenses is a well-known phenomenon [24][25]. Corneal lenses are typically fitted using the 3point-touch technique, which creates an apical contact area of 2-3 mm with minimal clearance over the apex, an intermediate clearance zone and a midperipheral contact annulus [26].…”
Section: Discussionmentioning
confidence: 99%
“…The second part of this study focused on changes to the corneoscleral profile in keratoconus eyes with regular specialty lens wear. Corneal warpage related to small-diameter corneal lenses is a well-known phenomenon [24][25]. Corneal lenses are typically fitted using the 3point-touch technique, which creates an apical contact area of 2-3 mm with minimal clearance over the apex, an intermediate clearance zone and a midperipheral contact annulus [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although corneal contact lenses vary according to fitting choice, they may cause changes in the curvature of the anterior and posterior surfaces due to the mechanical effect and the hypoxia they cause, and even if the contact lenses are removed, the stabilization process may take several weeks. 40 , 41 Because it is not possible to wait this long in practice, measurements were obtained from our patients at least 1 hour after lens removal, as per routine practice in our clinic. The extent to which the ORA device performs a true biomechanical assessment is controversial, as the pressure and waveform-based parameters obtained with the ORA are seriously affected by the geometric properties of the cornea (e.g., thickness) and by intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Corneal warpage appears to be gradually reversible after discontinuation of contact lens wear. Tsai et al reported that the discontinuation of rigid gas permeable (RGP) lens wear for six weeks may be necessary to ensure refractive stability before the initial examination for surgical correction of refractive error 39 . Hashemi et al reported that a two-week soft contact lens-free period seemed to be adequate for the cornea to stabilize 40 .…”
Section: Discussionmentioning
confidence: 99%